Perancangan Video Infografis Bahaya Merokok untuk Anak SD Menggunakan Teknik Motion Graphics - Nira Rusanti; Nindi Oktaviani; Faldi Hendrawan; Widya Adhariyanty Rahayu (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2018)
Health is one important aspect in human’s life. Nowadays, there are many disease that attack many people caused by bacteria, not only that bad habit and unhealthy lifestyle of human being also caused it. Smoking is one of unhealthy lifestyle. Moreover, smoking can give a horrible disease because cigarette contains of dangerous chemicals. If many children and teenagers have been started for being a smoker in their young age, there will be some bad impact that happen to them. Therefore, to prevent someone for being smoker, it will be better to use a media. One of the media that can be used is info graphic video. Additionally, there were two ways to gather the data for making an info graphic video, those are interview and literature review. In design process, the researcher tried to make the children in Elementary School interested and understood the video easily by making the illustration, animation with the language and image that were easy for them. Besides, by giving motion graphics technique in this video, it would be interesting for them. Info graphic video is one of visual communication media that consisted of some information and ideas about something that affected the children to get some responses. Info graphic video were made by busing some visual aesthetic elements such as images, colors, audio, and typography to make the video more interesting. In addition, it needed a software, Adobe After Effect, to make those visual aesthetic elements in order all of the components could be integrated each other’s. The researcher expected the info graphic video about smoking made the children in Elementary School understood about the video and gave a good response. On the other hand, from the result of questionnaire that was given to the children in Elementary School, the researcher got 75%. It means that the info graphic video was good for the children in Elementary School and it could be published as an educative media for Elementary School about the dangerous of smoking.